Traduções/adaptações dos romances-folhetins de Alexandre Dumas no Brasil: estudos de edição e cultura - Guimarães, Rosângela Maria Oliveira (2008)
Firstly, I situate the environment and describe the activities of two public libraries located at Vale do Paraíba, state of São Paulo, in the cities of Jacareí and São José dos Campos. Their collections include, among many cultural series, Alexandre Dumas serial novels. Next, the author s works are mapped, based on the above-mentioned collections. These works were translated and published in popular editions in Brazil, after the respective narratives had circulated in several Brazilian newspapers. This stage is related to the investigation of the constitutive and media processes of his works in the country. In this stage, the following works are used: texts by Jean-Ives Mollier and Jacques Migozzi, among others, which are included in the collection De l écrit à l écran (From writing to the screen); Roger Chartier s works about books, reading and edition (Leitura e Leitores na França do Antigo Regime / Reading and Readers in France at the time of the Ancien Régime, A Ordem do Livro / The Order of the Book, A Aventura do Livro / The Book Adventure); Jerusa Pires Ferreira s works on publishers and popular editions ( La Maison João do Rio ); and Brazilian authors who deal with the theme of reading and reception, like Márcia Abreu, Nelson Schapochnik, Marisa Lajolo, among others (the collections Leitura, História e História da Leitura no Brasil/Reading, History and the History of Reading in Brazil and Cultura Letrada no Brasil/ Literate Culture in Brazil). From the point of view of the history of the serial novel, the works Folhetim (Serial Novel), Caminhos do Imaginário (Mental Imagery Paths) and other texts by Marlyse Meyer offer important conceptual questions referring to the subject. To analyze the set of covers designed by Nico Rosso to Dumas novels of Coleção Saraiva (Saraiva Collection), a production in tune with the context of an emerging mass culture and with the popular book industry in Brazil, in this period, I used Charles Grivel s text Le passage à l écran (The passage to the screen) about hybrid literatures, and his work De la couverture illustré du roman populaire , among others. The aims of this research study are: to investigate the insertion and effects of the European literature of wide circulation in Brazil, through the inventory of Alexandre Dumas popular books; to build a panorama of the phenomenon of this adaptation universe and its implications; to observe editing processes and materials regarding this genre in Brazil, based on the collections of the public libraries of Vale do Paraíba, in São Paulo. The dissertation compares the recurrence of certain stereotyped themes that are recreated in the popular mental imagery and social inter-classes. Thus, it investigates narrative and fictional materials that came from Europe and were projected through the 19th, 20th and even the 21st centuries, in successive adaptations that maintain an inter-semiotic discourse in interaction. This study confirms that Dumas romances remained being read in the form of books in Brazil during the entire 20th century, after many of them left the foot of newspapers pages. The work was being intensely published during the period of the launch and dissemination of television among us (in the 1950s). It co-existed with the development of the cinema here and continues to be read in Internet times